A central role for polyprenol reductase in plant dolichol biosynthesis. (February 2021) - Van Gelder, Kristen; Virta, Lilia K.A.; Easlick, Jeremy; Prudhomme, Nicholas; McAlister, Jason A.; Geddes-McAlister, Jennifer; Akhtar, Tariq A.
Highlights: Metabolic engineering of dolichol biosynthesis in Nicotiana benthamiana . Polyprenol reductase is the bottleneck step in dolichol biosynthesis. Over-expressing three enzymes, CPT3, CPTBP and PPRD increases dolichol. Long-chain polyprenols are increased by 400-fold. Abstract: Dolichol is an essential polyisoprenoid within the endoplasmic reticulum of all eukaryotes. It serves as a membrane bound anchor onto which N -glycans are assembled prior to being transferred to nascent polypeptides, many of which enter the secretory pathway. Historically, it has been posited that the accumulation of dolichol represents the 'rate-limiting' step in the evolutionary conserved process of N -glycosylation, which ultimately affects the efficacy of approximately one fifth of the entire eukaryotic proteome. Therefore, this study aimed to enhance dolichol accumulation by manipulating the enzymes involved in its biosynthesis using an established Nicotiana benthamiana platform. Co-expression of a Solanum lycopersicum (tomato) cis -prenyltransferase (CPT) and its cognate partner protein, CPT binding protein (CPTBP), that catalyze the antepenultimate step in dolichol biosynthesis led to a 400-fold increase in the levels of long-chain polyprenols but resulted in only modest increases in dolichol accumulation. However, when combined with a newly characterized tomato polyprenol reductase, dolichol biosynthesis was enhanced by approximately 20-fold. We provide further evidence that in the aquatic macrophyte, Lemna gibba, dolichol is derived exclusively from the mevalonic acid (MVA) pathway with little participation from the evolutionary co-adopted non-MVA pathway. Taken together these results indicate that to effectively enhance the in planta accumulation of dolichol, coordinated synthesis and reduction of polyprenol to dolichol, is strictly required.